Experimental analysis and biaxial biomechanical behaviour of ex-vivo sheep trachea - Pandelani, Thanyani; Ngwangwa, Harry; Nemavhola, Fulufhelo (Frontiers in Materials, 2023)
Besides surgery, there are currently no other established methods for routine treatment of tracheal pathologies such a tracheal stenosis or tracheal and airway tumors. Even with several attempts to repair the infected trachea with artificial and natural prostheses, there is a need for the fundamental understanding of the tissue's mechanical behaviour. The purpose of this study was to investigate the mechanical behaviour of the tracheal tissue under biaxial tensile loading. Furthermore, the study examines the material properties of the tissue through a study of the model parameters for six constitutive models. Materials and methods: The fourteen (n = 14) specimens of sheep trachea (Vleis Merino) measured to be ~ 30 x 20 mm where only the effective area of ~ 25 x 16 mm was subjected to engineering strain. In this study, we assume that the tracheal tissue is anisotropic and incom-pressible, therefore we apply and study the material parameters from six models namely the Fung, Choi-Vito, Holzapfel (2000), Holzapfel (2005), Polynomial (Anisotropic) and Four-Fiber Family models. Results: The results show that the tracheal tissue is twice as stiff along the circumferential direction as it is along the longitudinal direction. It is also observed that the material properties are different (non-homogeneous) along the trachea. Conclusions: The findings of this study will benefit computational models for the study of tracheal diseases or injuries. Furthermore, these findings will assist in the development of regenerative medicine for different tracheal pathologies and in the bioengineering of replacement tissue in cases of damage.